2015
DOI: 10.1016/j.neuroimage.2015.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Sensory–motor networks involved in speech production and motor control: An fMRI study

Abstract: Speaking is one of the most complex motor behaviors developed to facilitate human communication. The underlying neural mechanisms of speech involve sensory-motor interactions that incorporate feedback information for online monitoring and control of produced speech sounds. In the present study, we adopted an auditory feedback pitch perturbation paradigm and combined it with functional magnetic resonance imaging (fMRI) recordings in order to identify brain areas involved in speech production and motor control. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
138
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(152 citation statements)
references
References 38 publications
12
138
0
Order By: Relevance
“…Consistent with this hypothesis, previous studies demonstrated that latency is normally increased when processing more versus less complex stimuli (Pakarinen et al, 2013;Polich, 2007;Pulvermüller & Shtyrov, 2006). Furthermore, robust evidence shows that the STG is particularly sensitive to Berrors^in one's own voice, acting as a more general deviance detector, both in active vocal production or passive-listening conditions (Behroozmand et al, 2015;Parkinson et al, 2012;Zheng et al, 2010). Indeed, auditory error cells, whose activity reflects the mismatch between sensory prediction and the incoming feedback, are thought to be located in the STG (planum temporal and posterior STG; Golfinopoulos et al, 2010).…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Consistent with this hypothesis, previous studies demonstrated that latency is normally increased when processing more versus less complex stimuli (Pakarinen et al, 2013;Polich, 2007;Pulvermüller & Shtyrov, 2006). Furthermore, robust evidence shows that the STG is particularly sensitive to Berrors^in one's own voice, acting as a more general deviance detector, both in active vocal production or passive-listening conditions (Behroozmand et al, 2015;Parkinson et al, 2012;Zheng et al, 2010). Indeed, auditory error cells, whose activity reflects the mismatch between sensory prediction and the incoming feedback, are thought to be located in the STG (planum temporal and posterior STG; Golfinopoulos et al, 2010).…”
Section: Discussionmentioning
confidence: 52%
“…Since the MMN is generated within supratemporal auditory cortical regions (Alho et al, 1996;Näätänen et al, 2007), this might suggest that the STG plays an important role in detecting deviance in SGVand NSV stimuli, even when participants' attention is focused elsewhere. Given the differential processing of one's own voice during speech production versus passive listening (Behroozmand et al, 2015;Golfinopoulos et al, 2010;Parkinson et al, 2012;Zheng et al, 2010;Zheng et al, 2013), the faster detection of a nonself than of a self-generated voice stimulus observed in our study might be specific of passivelistening contexts, wherein the reduced activation of sensorymotor mechanisms signals the biological relevance of detecting a nonself voice stimulus violating a regular and highly predictable auditory background. Moreover, the left STG has been consistently implicated in the processing of linguistic content and in the extraction of speech meaning conveyed by voice signals (e.g., Belin et al, 2011;Binder, 2000;DeWitt & Rauschecker, 2012;Obleser, Zimmermann, Van Meter, & Rauschecker, 2007).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…STG serves as functional integration area with partial overlap between speech perception and production mechanisms (Price, 2012). This functional overlap makes STG uniquely suited to detect and integrate auditory feedback during speech production (Behroozmand et al., 2015, 2016; Hickok & Poeppel, 2007; Parkinson et al., 2012; Paus, Perry, Zatorre, Worsley, & Evans, 1996; Tourville & Guenther, 2011; Tourville, Reilly, & Guenther, 2008). The STG cluster identified in the present study corresponds closely to an anterolateral region of Heschl's gyrus that electrocorticography data has linked to online voice error correction following rapid perturbations in auditory feedback (Behroozmand et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the more synchronous activity between the left and right IFGpt, simultaneous bilinguals had greater connectivity between the IFGpt and a distributed system of cognitive control areas, including the dorsolateral prefrontal cortex and inferior parietal lobule, within the frontoparietal executive control circuit (Cole and Schneider, 2007;Vincent et al, 2008;Spreng et al, 2010;Wang et al, 2014;Behroozmand et al, 2015), a system of brain regions that manages cognitive function across a wide array of conditions and facilitates rapid changes in behavior that require enhanced attention. García-Pentó n (2013) recently identified increased efficiency of the frontoparietal subnetwork for early Spanish-Basque bilinguals, and there is emerging evidence that this control system persists in older bilingual adults (Grady et al, 2015).…”
Section: Discussionmentioning
confidence: 99%